Antibacterial Activity of Ethanol Extract of Arabian Bidara Leaves (Ziziphus spina-christi L) and Bioautography TLC Analysis Against Pathogenic Bacteria - Herlina Rante; Marni Pabisa; Burhanuddin Taebe (Jurusan Biologi Universitas Negeri Makassar, 2023)
The Ziziphus spina-christi L. plant, commonly known as Arabian bidara, are rich in potentially health-beneficial compounds, particularly those with antibacterial properties. This research aimed to investigate the effectiveness of an ethanolic leaf extract in inhibiting the growth of pathogenic bacteria. The leaves were subjected to maceration using 70% ethanol, followed by an assessment of their antibacterial properties using the agar diffusion method. Subsequently, the active extract was analyzed through bioautography using thin-layer chromatography (TLC), and its phytochemical spotted was screened. The results of the antibacterial activity using the ethanolic leaf extract revealed that it exhibited antibacterial activity when applied at a concentration of 2 mg per paper disk. Subsequently, it showed inhibition zones with diameters of 19.44 mm for Bacillus subtillis; Escherichia coli (17.06 mm); Staphylococcus aureus (16.32 mm); Pseudomonas aeruginosa (12.96 mm), and Salmonella typhi (14.50 mm). The TLC-bioautography analysis of the ethanolic leaf extract demonstrated inhibitory activity against Bacillus subtillis of Rf value with 0.96, Escherichia coli (0.31) and Staphylococcus aureus (0.89). However, no inhibitory activity was observed against Salmonella typhi. The phytochemical screening results suggested the presence of flavonoids, terpenoids, and tannins in the ethanolic leaf extract.